A QUALITATIVE STUDY ON STUDENTS BEHAVIOR TOWARD SUDDEN ONLINE LEARNING POLICY - Darman Fauzan Dhahir (Journal of Information Technology and Its Utilization, 2020)
Education stakeholders in Indonesia have made rapid adjustments due to the Coronavirus disease 2019 (COVID-19) pandemic outbreak that demanded social distancing to avoid it. Yayasan Pendidikan Budi Utomo Makassar also issued a policy that changed the learning methods from offline to online. The current research was aimed to find out the behaviors of students facing this sudden policy. It was conducted with a qualitative approach. Data were collected from observations of several Yayasan Pendidikan Budi Utomo Makassar’s students. The results showed that students obeyed the policy. Some of them learned and did the tasks as expected, but some others skipped the lessons, postponed doing assignments, and complained through the online communication media that had been provided.